P819 Influence of knowledge, attitude, motivation on willingness of mothers for their daughters to undergo HPV vaccination. (14th July 2019) - Bravo, Sybil Lizanne
Abstract : Background: Cervical cancer is second leading cancer and cause of morbidity/mortality among Filipinas. Human papillomavirus (HPV) is a necessary cause of cervical cancer. A primary mode of prevention is use of vaccines. Before vaccinations are implemented, sociocultural issues should be addressed. The aim was to determine association of knowledge, attitude and motivational factors of mothers on their willingness for their daughters (aged 9–13 years) to undergo vaccination. Methods: This was a cross-sectional study with a pretested and validated survey given to 352 mothers. Results: 97.18% of women were willing to have the vaccine for their children. One-third of mothers had high knowledge on use of vaccines (34.93%). Women who reached college, had youngest child 11 - 13 years, with annual income ≥PHP 60, 000, non-Catholic, and who never to a few times/year attended Church had higher knowledge. More believed getting the vaccine would not affect girl's sexual activity. Most agreed they were not viewed as bad parents. There were agreeing responses from positive attitude, and more disagreeing responses in negative attitude (p= 0.01). More mothers agreed cost was prohibitive, with giving 2 doses, and were willing to follow doctors' recommendations. There was no difference in agreeing responses between positive and negative motivating factors (p= 0.79). Likelihood of willingness on vaccination was twice as knowledge score and scores on positive attitude items increased. Odds of willingness increased as scores on negative attitude decreased. Conclusion: Role of knowledge and attitudes on negative perceptions on the vaccine were important predictors of willingness of mothers toward vaccination. In developing countries such as ours, there is strong need to increase knowledge of HPV, cervical cancer, and prophylactic vaccines to increase willingness of Filipino mothers to have their daughters immunized. Physicians and government agencies should put priority on HPV vaccination, making concerted efforts to decrease negative attitudes. Disclosure: No significant relationships.